Morphology characteristic and tuber content of yard cultivated Canna indica (ganyong) in Cibinong, West Java, Indonesia - NITA NORIKO; YORIANTA HIDAYAT SASAERILA; SITI ANISAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Noriko N, Sasaerila YH, Anisah S. 2024. Morphology characteristic and tuber content of yard cultivated Canna indica (ganyong) in Cibinong, West Java, Indonesia. Biodiversitas 25: 2586-2593. Canna indica L. (ganyong) tubers have the potential to be an alternative food and functional food. This study aims to obtain morphology characteristics, including the content of white tubers of C. indica planted in yards in the Cibinong; research methodology by conducting surveys and laboratory analysis. The results showed C. indica can grow in the yard without special treatment. At the age of 8 months, the average 59.8 cm of plant height, 10.8 numbers of leaves, 0.80 mm leaf thickness, 9.14 cm stem diameter, 24.51 cm2 leaf area, 112.64 g dry weight of tuber, 6.9 g dry weight of stem, 6.81 g dry weight of leaves at 34.3°C temperature, 59% humidity, 20086 lux light intensity, 4.85 soil pH, 2.3% organic C, 0.62% total N, 32.13% P2O5, 6.08% K2O, 0.51 me Ca, 0.36 me Mg, 0.31 me K, 0.5 me Na, 5.44 me/100 gr CEC, 3.71 (mg FDA g-¹soil d.w. h-¹) soil enzyme activity and 1.66 (g/cm³) bulk density. The flour from tubers contains 0.58% ash, 0.15% lipid, 1.01% protein, 1.11% crude fiber, 12.78% carbohydrates, 56.51 kcal calories, alkaloid, saponin, flavonoid, triterpenoid, and low antioxidant. Planting in the yard is recommended in the shade of sunlight. Watering and fertilizing including microelements are also required.